Yeast RAD6 encoded ubiquitin conjugating enzyme mediates protein degradation dependent on the N-end-recognizing E3 enzyme. - Sung, P (1991)
The RAD6 gene of Saccharomyces cerevisiae encodes a 20 kd ubiquitin conjugating (E2) enzyme that is required for DNA repair, DNA damage-induced mutagenesis, and sporulation. Here, we demonstrate a novel activity of RAD6 protein--its ability to mediate protein degradation dependent on the N-end-recognizing ubiquitin protein ligase (E3). In reaction mixtures containing E1, E3 and the ubiquitin specific protease from rabbit reticulocytes, RAD6 is as effective as mammalian E214k in E3 dependent ubiquitin--protein conjugate formation and subsequent protein degradation. The ubiquitin conjugating activity of RAD6 is required for these reactions as indicated by the ineffectiveness of the rad6 Ala88 and rad6 Val88 mutant proteins, which lack the ability to form a thioester adduct with ubiquitin and therefore do not conjugate ubiquitin to substrates. We also show that the highly acidic carboxyl-terminus of RAD6 is dispensable for the interaction with E3, and that purified S. cerevisiae E2(30k), product of the UBC1 gene, does not function with E3. These findings demonstrate a specific interaction between RAD6 and E3, and highlight the strong conservation of the ubiquitin conjugating system in eukaryotes. We suggest a function for RAD6 mediated E3 dependent protein degradation in sporulation, and discuss the possible role of this activity during vegetative growth.